Activation of alpha(2)-adrenergic receptors into the lateral parabrachial nucleus enhances NaCl intake in rats - Andrade, CAF; Barbosa, S. P.; De Luca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2004)
Water and NaCl intake is strongly inhibited by the activation of alpha(2)-adrenergic receptors with clonidine or moxonidine (alpha(2)-adrenergic/imidazoline agonists) injected peripherally or into the forebrain and by serotonin and cholecystokinin in the lateral parabrachial nucleus (LPBN). Considering that alpha(2)-adrenergic receptors exist in the LPBN and the similar origin of serotonergic and adrenergic afferent pathways to the LPBN, in this study we investigated the effects of bilateral injections of moxonidine alone or combined with RX 821002 (alpha(2)- adrenergic antagonist) into the LPBN on 1.8% NaCl and water intake induced by the treatment with s.c. furosemide (10 mg/kg)+captopril (5 mg/kg). Additionally, we investigated if moxonidine into the LPBN would modify furosemide+captopril-induced c-fos expression in the forebrain. Male Holtzman rats with cannulas implanted bilaterally in the LPBN were used. Contrary to forebrain injections, bilateral LPBN injections of moxonidine (0.1, 0.5 and 1 nmol/0.2 mul) strongly increased furosemide+captopril-induced 1.8% NaCl intake (16.6 +/- 2.7, 44.5 +/- 3.2 and 44.5 +/- 4.3 ml/2 h, respectively, vs. vehicle: 6.9 +/- 1.5 ml/2 h). Only the high dose of moxonidine increased water intake (23.3 +/- 3.8 ml/2 h, vs. vehicle: 12.1 +/- 2.6 ml/2 h). Prior injections of RX 821002 (10 and 20 nmol/0.2 mu1) abolished the effect of moxonidine (0.5 nmol) on 1.8% NaCl intake. Moxonidine into the LPBN did not modify furosemide+captopril-induced c-fos expression in forebrain areas related to the control of fluid-electrolyte balance. The results show that the activation of LPBN a2-adrenergic receptors enhances furosemide+captopril-induced 1.8% NaCl and water intake. This enhancement was not related to prior alteration in the activity of forebrain areas as suggested by c-fos expression. Previous and present results indicate opposite roles for alpha(2-)adrenergic receptors in the control of sodium and water intake according to their distribution in the rat brain. (C) 2004 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; thirst; moxonidine; electrolyte balance; ingestive behavior